Clinical standards for the assessment, management and rehabilitation of post-TB lung disease - Migliori, G B; Marx, F M; Ambrosino, N; Zampogna, E; Schaaf, H S; van der Zalm, M M; Allwood, B; Byrne, A L; Mortimer, K; Wallis, R S; Fox, G J; Leung, C C; et al. (The international journal of tuberculosis and lung disease, 2021)
Increasing evidence suggests that post-TB lung disease (PTLD) causes significant morbidity and mortality. The aim of these clinical standards is to provide guidance on the assessment and management of PTLD and the implementation of pulmonary rehabilitation (PR). A panel of global experts in the field of TB care and PR was identified; 62 participated in a Delphi process. A 5-point Likert scale was used to score the initial ideas for standards and after several rounds of revision the document was approved (with 100% agreement). Five clinical standards were defined: Standard 1, to assess patients at the end of TB treatment for PTLD (with adaptation for children and specific settings/situations); Standard 2, to identify patients with PTLD for PR; Standard 3, tailoring the PR programme to patient needs and the local setting; Standard 4, to evaluate the effectiveness of PR; and Standard 5, to conduct education and counselling. Standard 6 addresses public health aspects of PTLD and outcomes due to PR. This is the first consensus-based set of Clinical Standards for PTLD. Our aim is to improve patient care and quality of life by guiding clinicians, programme managers and public health officers in planning and implementing adequate measures to assess and manage PTLD.